An Organic Chemist's Guide to Mediated Laccase Oxidation. (18th October 2022) - Obleser, Katharina; Kalaus, Hubert; Seidl, Bernhard; Kozich, Martin; Stanetty, Christian; Mihovilovic, Marko D.
Abstract: Laccases are oxidases that only require O2 as a terminal oxidant. Thus, they provide an attractive green alternative to established alcohol oxidation protocols. However, laccases typically require catalytic amounts of mediator molecules to serve as electron shuttles between the enzyme and desired substrate. Consequently, laccase‐mediator systems are defined by a multitude of parameters such as, e. g., the choice of laccase and mediator, the respective concentrations, pH, and the oxygen source. This complexity and a perceived lack of comparable data throughout literature represent an entry burden into this field. To provide a solid starting point, particularly for organic chemists, we herein provide a time‐resolved, quantitative laccase and mediator screening based on the oxidation of anis alcohol as model reaction. We measured the redox potentials of mediators under the reaction conditions to relate them to their performance. Lastly, for particularly efficient laccase‐mediator pairs, we screened important reaction parameters, resulting in an optimized setup for mediator‐assisted laccase catalyzed oxidations. Abstract : The mediator‐assisted laccase‐catalyzed oxidation of alcohols is a green alternative to established classical synthetic protocols. However, the interaction between laccases, mediators and oxygen comprises a highly complicated, multivariate system. We present a detailed comparative study evaluating the most important components and parameters via an anis alcohol model system.